Nonlinear modelling and control of a quadplane - Sheikh Moheed Muzaffar (2018)
Vertical Take-off and Landing (VTOL) capabilities of fixed-wing UAV is currently being researched because of its ability to takeoff/land like rotor-craft, yet transition to forward flight like a fixed-wing. This removes the drawback of longer runways needed for takeoffs/landings and ensures that efficient flight with higher speed, endurance and range is achieved. However, control of VTOL UAV’s is not an easy task, because of the transition phase involved where the aerodynamic forces acting on the body become complex. To be able to better control it, accurate estimation of aerodynamic forces which drive the nonlinear dynamics is needed. In this work, a nonlinear aerodynamic model for a quadplane is developed that predicts the unsteady lift and drag forces produced during the transition phase. The aerodynamic modeling is based on an unsteady Lumped Vortex Method. The results of the aerodynamic model are incorporated in 3 DoF longitudinal nonlinear model of a quadplane. A PID controller is also implemented to fix the altitude and attitude of the vehicle.